Liquidity and Firm Market Value: The Moderating Role of Firm Size - Khodijah Ishak; Muhammad Isa Selamat (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
A strong market valuation signals robust future growth prospects, attracting capital investment as investors perceive potential for returns. Conversely, a declining market value may indicate underlying management inefficiencies, deterring investor confidence. This study investigates the impact of liquidity ratios on firm market value, with particular emphasis on the moderating role of firm size in this relationship. Utilizing a sample of non-financial firms listed on the Indonesia Stock Exchange from 2016 to 2022, this research applies panel data analysis through the Ordinary Least Squares (OLS) method to test the proposed hypotheses. The findings reveal that liquidity ratios—specifically the current ratio, quick ratio, and cash ratio—negatively affect firm market value. Moreover, the results suggest that firm size significantly moderates the relationship between liquidity ratios and market value. This study enriches the literature by providing nuanced insights into the optimal management of corporate liquidity to enhance firm market value. From a practical standpoint, the research offers valuable implications for managerial decision-making, particularly in crafting debt and asset management strategies that influence firm valuation.